Comparison of 10 vs. 20 min neuromuscular training for the prevention of lower extremity injuries in male youth football: A cluster randomised controlled trial. Issue 19 (1st October 2020) - Rahlf, Anna Lina; Zech, Astrid
ABSTRACT: The aim of this study was to compare the effects of 20 min neuromuscular training with a programme of 10 min in youth football players. 342 (15.4 ± 1.7 years) male football players from 18 teams were included, and cluster-randomized by team into two intervention groups. Both groups performed an injury prevention programme twice a week over five months using the same exercises but a different duration. The first intervention group (INT10, n = 175) performed the programme for 10 min, the second intervention group (INT20, n = 167) for 20 min. Primary outcomes were lower extremity (LE) injuries. Secondary outcomes were injury type, severity, mechanism and compliance to the intervention. 13 teams with 185 players were included for final analysis. No significant group difference was found between INT10 (6.37 per 1000 h) and INT20 (7.20 per 1000 h) for the incidence rate ratio of the lower extremities (IRR = 1.03, 95% confidence interval 0.59, 1.79), nor for the distribution of injury location, type, severity or mechanism. The results show that performing preventive exercises for 10 min is no less effective than 20 min in youth football players. Shorter training sessions can, therefore, be effectively used for injury prevention. Trial registration: DRKS00015282